Study Protocol: Determining Research Priorities of Young Albertan Families (The Family Research Agenda Initiative Setting Project—FRAISE)—Participatory Action Research - Bright, Katherine S.; Ginn, Carla; Keys, Elizabeth M.; Brockway, Meredith L.; Tomfohr-Madsen, Lianne; Doane, Stephanie; Benzies, Karen (Frontiers in Public Health, 2018)
Introduction: Pregnancy and childrearing can be an exciting and stressful time for new parents. The maternal-child health landscape has changed dramatically over the last few decades and research priorities need to address these rapid changes. There have been limited attempts to engage and collaborate with members of the public to develop research priorities for families who are expecting or parenting an infant to age 24 months. The work that has been completed has attempted to identify parental preference for information delivery and barriers to uptake of parenting programs but has not investigated parental research priorities. Methods: In collaboration with provincial research units and strategic clinical networks (SCN), we will use principles of participatory action research (PAR) as our theoretical framework/method, and a modified James Lind Alliance priority setting approach to prioritize a list of research questions that parents/knowledge users believe will support the health of their families. This will result in a top 10 list of parent/knowledge user-identified research priorities. This project will consist of three phases. In the first phase, we developed a steering committee of parents/knowledge users, healthcare providers, community agencies, and researchers to design a survey about health priorities for families. In the second phase, we will distribute the survey to diverse groups of parents/knowledge users/providers and hold a series of meetings to identify and prioritize potential questions from new parents about health issues from conception to age 24 months. In the third phase, we will collaboratively disseminate and translate findings. Discussion: This study will highlight parental health concerns and recommend parent-identified research priorities to inform future research projects needed to support the health of families between conception to age 24 months. Understanding the health research priorities of families in the community will help ensure future research contributes to meaningful changes in the health of young children, parents/knowledge users, and families. Ethics: This study and protocol have received ethical approved from the Conjoint Health Research Ethics Board at the University of Calgary (REB17-0014). Dissemination: The top 10 research priorities will be published and additional findings from the study will be distributed through pamphlets and newsletters.